2012
DOI: 10.1093/infdis/jis509
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Antiviral Effectiveness in Influenza Virus A Subtype H5N1

Abstract: Oseltamivir is especially effective for treating H5N1 infection when given early and before onset of respiratory failure. The effect of viral clade on fatality and treatment response deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 24 publications
5
49
0
Order By: Relevance
“…Similar adaptive changes have been reported to occur human virus isolates of other avian viruses (e.g., clade 0 or clade 1 H5N1 viruses) as they adapt in humans (31). In contrast, PB2-E627K changes are fixed within avian viruses of the clade 2.2 lineage that are now endemic in Egypt, with evidence of reduced severity of human disease caused by this lineage (32).…”
Section: Discussionsupporting
confidence: 66%
“…Similar adaptive changes have been reported to occur human virus isolates of other avian viruses (e.g., clade 0 or clade 1 H5N1 viruses) as they adapt in humans (31). In contrast, PB2-E627K changes are fixed within avian viruses of the clade 2.2 lineage that are now endemic in Egypt, with evidence of reduced severity of human disease caused by this lineage (32).…”
Section: Discussionsupporting
confidence: 66%
“…In addition, Oseltamivir therapy starting on day 7 of illness did not prevent death, although the NA sequence data predicted susceptibility. It may be related to the delay in starting antiviral therapy as antiviral therapy can shorten the duration of viral shedding and reduced mortality in hospitalized patients with severe influenza if prescribed during the first 3 days of illness (30)(31)(32).…”
Section: Epidemiological Investigationmentioning
confidence: 99%
“…In Indonesia the case fatality rate is 83% (153/185) [1]. We recently reported the impact of treatment on the clinical course of influenza H5N1 and showed that though treatment with oseltamivir within 48 hours offers significant benefits in terms of survival; the benefits of treatment persist in terms of reduced case fatality rates, though to a lesser extent, even if treatment is delayed up to 6 to 8 days after symptom onset [2,3]. Given the very high mortality rates associated with H5N1 infection in Indonesia and the known association with delays in initiating treatment, it is important to determine whether delays occur across the country or whether some provinces experience longer delays than others, and whether delays are the result of patients delaying seeking health care or whether delays in the health care service itself are important.…”
Section: Introductionmentioning
confidence: 99%